Operating theatre time, where does it all go? A prospective observational study. (15th December 2014) - Travis, Elizabeth; Woodhouse, Sarah; Tan, Ruth; Patel, Sandeep; Donovan, Jason; Brogan, Kit
Abstract : Objective To assess the accuracy of surgeons and anaesthetists in predicting the time it will take them to complete an operation or procedure and therefore explain some of the difficulties encountered in operating theatre scheduling. Design Single centre, prospective observational study. Setting Plastic, orthopaedic, and general surgical operating theatres at a level 1 trauma centre serving a population of about 370 000. Participants 92 operating theatre staff including surgical consultants, surgical registrars, anaesthetic consultants, and anaesthetic registrars. Intervention Participants were asked how long they thought their procedure would take. These data were compared with actual time data recorded at the end of the case. Primary outcome measure Absolute difference between predicted and actual time. Results General surgeons underestimated the time required for the procedure by 31 minutes (95% confidence interval 7.6 to 54.4), meaning that procedures took, on average, 28.7% longer than predicted. Plastic surgeons underestimated by 5 minutes (−12.4 to 22.4), with procedures taking an average of 4.5% longer than predicted. Orthopaedic surgeons overestimated by 1 minute (−16.4 to 14.0), with procedures taking an average of 1.1% less time than predicted. Anaesthetists underestimated by 35 minutes (21.7 to 48.7), meaning that, on average, procedures took 167.5% longer than they predicted. The four specialty mean time overestimations or underestimations are significantly different from each other (P=0.01). The observed time differences between anaesthetists and both orthopaedic and plastic surgeons are significantly different (P<0.05), but the time difference between anaesthetists and general surgeons is not significantly different. Conclusion The inability of clinicians to predict the necessary time for a procedure is a significant cause of delay in the operating theatre. This study suggests that anaesthetists are the most inaccurate and highlights the potential differences between specialties in what is considered part of the "anaesthesia time."